Layer-separated distribution of nitrogen doped graphene by wrapping on carbon nitride tetrapods for enhanced oxygen reduction reactions in acidic medium - Unni, SreeKuttan M.; Illathvalappil, Rajith; Gangadharan, Pranav K.; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Chemical Communications, 2014)
Layer-separated 3D nitrogen doped graphene (NG) with an accessible interstitial surface and modulated activity characteristics for oxygen reduction in acidic medium could be prepared by wrapping NG sheets on in situ generated carbon nitride (CNx) tetrapods.

High-index faceted Au nanocrystals with highly controllable optical properties and electro-catalytic activity - Rajendra, Ranguwar; Gangadharan, Pranav K.; Tripathi, Shalini; Kurungot, Sreekumar; Ballav, Nirmalya (Nanoscale, 2016)
We introduce a new and naturally abundant mild reducing agent, tannic acid, to improve the seed-mediated growth method for the synthesis of elongated tetrahexahedral Au nanocrystals enclosed with high-index (730) planes, at room-temperature. The control of the dimensions, plasmonics and electro-catalysis of such high-index faceted nanocrystals is remarkable.

Nitrogen-doped graphene with a three-dimensional architecture assisted by carbon nitride tetrapods as an efficient metal-free electrocatalyst for hydrogen evolution - Gangadharan, Pranav K.; Unni, SreeKuttan M.; Kumar, Nandha; Ghosh, Prasenjit; Kurungot, Sreekumar (Chemelectrochem, 2017)
Current polymer membrane-based electrolyzers use Pt as a cathode catalyst for efficient reduction of water. The high cost of Pt-based catalysts forces researchers to develop alternative electrocatalysts. Here, a simple strategy has been proposed to synthesize a metal-free electrocatalyst for the hydrogen evolution reaction (HER) by high-temperature annealing of graphene oxide-coated melamine foam. The prepared catalyst possesses both structural and functional advantages with its three-dimensional (3D) interconnected arms of carbon nitride (CNx) backbone wrapped with nitrogen-doped graphene (N-RGO) sheets (CNx@N-RGO). CNx@N-RGO faces only a 193 mV overpotential to achieve a current density of 10mAcm(-2), which is far superior to the previously reported Pt-free systems. Along with the high exchange current density 34.7 x 10(-6)A cm(-2) and low Tafel slope of 54 mV dec(-1), CNx@N-RGO follows a Volmer-Heyrovsky mechanism for the HER. DFT calculations show that the synergy between CNx and N-RGO facilitates good electrical coupling between the two moieties and provides optimal binding to H+ ions on the catalyst that, in turn, results in efficient reduction of hydrogen ions.
Keywords: carbon nitride; Density functional theory; electrocatalyst; hydrogen evolution reaction; nitrogen doped graphene

Cubic palladium nanorattles with solid octahedron gold core for catalysis and alkaline membrane fuel cell applications - Singh, Prem; Sonika; Gangadharan, Pranav K.; Khan, Ziyauddin; Kurungot, Sreekumar; Jaiswal, Amit (ChemCatChem, 2019)
Herein, we report the synthesis of palladium nanorattles (Au-Pd NRTs) comprising of a gold octahedral core caged within a thin porous cubic palladium shell. The introduction of core-shell and porous architecture was realized by combining seed mediated and galvanic replacement reaction techniques. Next, we examined the catalytic efficiency of the nanocatalyst in comparison with solid palladium nanocube (Pd-NC) of similar size for the degradation of p-nitrophenol and organic dyes. The rate constant of Au-Pd NRTs was found nearly 12 times higher than the Pd-NCs. Further, we exploited our catalyst for electrochemical oxygen reduction reaction (ORR) and observed its high intrinsic ORR activity. Compared with commercialized Pt/C, the Au-Pd NRT displayed nearly comparable onset and half-wave potential values and excellent durability upon potential cycling. The system level validation in a single-cell mode of alkaline exchange membrane fuel cell also confirms the efficiency of the present catalyst to serve as a potential cathode catalyst for realistic device applications.
Keywords: alkaline exchange membrane fuel cell; electrocatalysis; nanorattles; ORR; Pd nanoparticle

In situ preparation of ionomer as a tool for triple-phase boundary enhancement in 3D graphene supported Pt catalyst - Gangadharan, Pranav K.; Vijayakumar, Vidyanand; Nediyirakkal, Shijil A.; Fernandez, Roshni Tresa; Siddharthan, V. Adhrika; Kurungot, Sreekumar (Advanced Sustainable Systems, 2021)
For improving the performance of platinum electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs), it is important to enhance the Pt utilization level in the catalyst systems. A high performing electrocatalyst (Pt/3DNG) is developed for PEMFC applications by using nitrogen-doped 3D graphene (3DNG) as the support material and an in situ grafted active ``triple-phase boundary'' to more precisely control the formation of the proton conducting ionomer interface at the active sites. Considering the 3D morphology of the system, during the electrode fabrication for realistic single-cell evaluation, the concept of in situ generation of the proton conducting-ionomer based ``active triple-phase boundary'' is introduced, which could potentially replace the conventional method of using Nafion ionomer for the electrode preparation. The monomers owing to their small-size can access the pores and inner regions of the 3DNG support, which on UV-curing, undergo polymerization and transform into an ionomer with an extended interfacial network into the nanoregimes of 3DNG. Single cell evaluation of the membrane electrode assembly in a high-temperature PEMFC by using phosphoric acid doped polybenzimidazole membrane demonstrates the utility of the present strategy.
Keywords: electrocatalysts; fuel cells; graphene; oxygen reduction reaction

Seed-mediated growth of Pt on high-index faceted Au nanocrystals: the ag lining and implications for electrocatalysis - Roy, Debashree; Rajendra, Ranguwar; Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar; Ballav, Nirmalya (ACS Applied Nano Materials, 2021)
Bimetallic Au@Pt nanocrystals (NCs) offer a unique combination of plasmonic and catalytic properties and are a growing field of research. Herein, we report an unusual observation in the behavior of silver ions (Ag+) which was found to play a dominant role in dictating the Pt deposition in a seed-mediated growth method. `While the literature is replete with various instances of Ag-assisted Pt deposition whereby higher concentration of Ag+ translates into a thicker Pt shell, in the present study, contradictory observations were made. In the presence of lower amounts of Ag+, thick Pt shells were visualized, while at higher concentrations of Ag+, the extent of Pt deposition via the galvanic replacement reaction was reduced. Additionally, the presence of Ag was deemed necessary for the Pt deposition to take place, either in the form of an underpotential deposition layer on the Au NCs or by introducing Ag+ in the growth solution. We have demonstrated our findings on two different Au NCs enclosed with high-index facets, concave cuboid, and elongated tetrahexahedra, which mirror similar observations and provide generality to our claim. To the best of our knowledge, the time required for Pt deposition on the Au core in the present work is the least among the reported seed-mediated routes. Furthermore, this work, besides presenting a facile and general route for the amalgamation of catalytic and plasmonic properties in hybrid Pt-Au NCs, sheds light on the mechanistic aspects of Ag-assisted wet-chemical generation of bimetallic Au@Pt NCs. The overall electrocatalytic performance of our Au@Pt NCs toward the oxygen reduction reaction was realized to be impressive.
Keywords: bimetallic nanostructure; galvanic replacement reaction; high-index facet; oxygen reduction reaction; seed-mediated growth; underpotential deposition

Toward pH independent oxygen reduction reaction by polydopamine derived 3D interconnected, iron carbide embedded graphitic carbon - Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2021)
Recent advancements on the development of nonprecious electrocatalysts with iron (Fe) incorporated active centers have generated confidence on realizing cost-effective proton exchange membrane fuel cells (PEMFCs). However, most of these catalysts that emerged as a substitution for the platinum supported on carbon (Pt/C) catalysts in oxygen reduction reaction (ORR) are active under basic conditions, and their feasibility in PEMFCs remains as a challenge. In this scenario, this work reports the synthesis of a Pt-free oxygen reduction electrocatalyst prepared by the annealing of polydopamine grown melamine foam. The prepared catalyst has a three-dimensional (3D) interconnected bilayer network structure possessing the carbon nitride backbone wrapped by graphitic carbon layer bearing iron carbides and nitrides as the active centers (3DFePDC). Interestingly, the 3D-FePDC catalyst displayed an ORR activity both under acidic and basic conditions. Whereas the ORR performance of 3D-FePDC closely matches that of the commercial Pt/C in the basic medium, it displays only a low overpotential value of 60 mV under acidic conditions compared to its Pt counterpart. The kinetics of ORR on 3DFePDC is found to be similar to the four-electron (4e) reduction pathway displayed by Pt/C. Testing of a PEMFC in a single cell mode by using 3D-FePDC as the cathode catalyst and Nafion membrane delivered a maximum power density of 278 mW cm(-2), which is a promising value expected from a system based on the nonprecious metal cathode. Ultimately, as a cost-effective catalyst that can effectively perform irrespective of the pH conditions, 3D-FePDC offers significant prospects in the areas like fuel cells and metal-air batteries which work in acidic and/or basic conditions.
Keywords: acidic medium; electrocatalyst; fuel cell; graphitic carbon; Iron carbide; nitrogen doping; nonprecious metal; oxygen reduction reaction

Advanced 3D network of N-doped graphitic carbon with FeNi alloy embedding for high-performance rechargeable Zn-air batteries - Pandikassala, Ajmal; Kurian, Maria; Gangadharan, Pranav K.; Torris, Arun; Kurungot, Sreekumar (Advanced Sustainable Systems, 2024)
Despite the significant progress in Zn-air batteries (ZABs), their widespread use in the rechargeable sector is hindered due to the scarcity of efficient bifunctional oxygen catalysts that can catalyze both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). To address this, an ORR/OER bifunctional electrocatalyst is designed with ultrafine alloyed FeNi nanoparticles encapsulated in a 3D interconnected N- doped carbon network structure, featuring a carbon nitride backbone enclosed in graphitic carbon. The FeNi electrocatalyst (3DFeNiPDC) showed good bifunctional activity toward both ORR and OER in the basic medium with a low overpotential value of 30 mV for ORR and 6 mV for OER compared to its state-of-the-art counterparts Pt/C, and RuO2, respectively. Utilizing 3DFeNiPDC in a rechargeable Zn-air battery (RZAB) yields an open circuit voltage (OCV) of 1.35 V, a maximum power density of 232 mW cm-2, and an energy density of 707 W h kg-1. Additionally, a flexible RZAB employing 3DFeNiPDC demonstrates an OCV of 1.4 V with various bending angles. These finding suggest 3DFeNiPDC as a viable alternative to noble metal-based RZABs, offering superior bifunctional electrocatalytic activity and stability, particularly with its enhanced air-breathing properties facilitating improved operability under practical conditions. The bifunctional electrocatalytic activity of FeNi alloy nanoparticles embedded in a 3D- interconnected N-doped graphitic carbon (3DFeNiPDC) for both oxygen reduction and oxygen evolution is studied. The 3D architecture and core-shell characteristics of FeNi alloy nanoparticles provide better activity and stability for oxygen electrocatalysis. The electrocatalytic activity of 3DFeNiPDC has been exploited for liquid-state and solid-state flexible rechargeable zinc-air batteries. image
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery